Correlation of Dual-Energy X-Ray Absorptiometry and Quantitative Computerized Tomography in Detection of Osteoporosis among Postmenopausal Women: Dual-Energy X-Ray Absorptiometry and Quantitative Computerized Tomography for Osteoporosis - Yusuf, Shazia; Kashmir, Saba Binte; Abbasi, Muhammad Afzal; Riaz, Humaira; Kamran, Rana Muhammad Haseeb; Zeb, Romasa (Pakistan Journal of Health Sciences, 2024)
Osteoporosis is a serious health responsibility for clinicians, especially in postmenopausal patients. Dual-energy x-ray absorptiometry is currently the gold standard for the detection of osteoporosis, though its accuracy may be compromised due to concomitant degenerative changes. Objectives: To find out the detection rate of osteoporosis in women who have gone through menopause using both dual-energy X-ray absorptiometry and quantitative computerized tomography and to identify correlations between the two. To evaluate quantitative computerized tomography as a possible future imaging modality that can address the constraints of dual-energy x-ray absorptiometry. Methods: From June 2016 to July 2017, this cross-sectional study was carried out in the radiology Departments of Capital Hospital and Nuclear Medicine, Oncology and Radiotherapy Institute Hospital, Islamabad. With informed consent, seventy postmenopausal women participated. T-scores were calculated for quantitative computerized tomography and dual-energy x-ray absorptiometry, and data analysis, including the Pearson correlation coefficient, was conducted using SPSS-17. Results: The study included postmenopausal women aged 45–70, with menopause lasting over two years. The mean T-scores for quantitative computerized tomography and dual-energy x-ray absorptiometry were -2.4 ± 1.4 SD and -2.1 ± 1.3 SD, respectively. A strong positive correlation was established between quantitative computerized tomography and dual-energy x-ray absorptiometry T-scores (r=0.808; p<0.05). Conclusions: It was concluded that the study showed a constructive association between the T-scores obtained using quantitative computerized tomography and dual-energy x-ray absorptiometry, thus suggesting that quantitative computerized tomography can be used as an alternative to dual-energy x-ray absorptiometry in the detection of osteoporosis.